Adsorbent Size's Impact On Removing Heavy Metals - Mycelia Paradise; Yudha Agung Pratama (Jurusan Teknik Lingkungan, FTM, Universitas Pembangunan Nasional “Veteran” Yogyakarta, 2023)
Numerous variables affect how well adsorption works. The material's surface area is a crucial factor in adsorption. The speed of adsorption by powder material is greater than by granular material. It is related to its surface area. The study aimed to compare the changes of dissolved heavy metals and water pH after adsorption using 60 and 100-mesh adsorbent. A hot plate stirrer was used to carry out adsorption for 5, 10, and 15 minutes. The result showed that the pH of the water changed to neutral after adsorption using 100 mesh adsorbent. Water pH did not meet quality standards after adsorption with 60 mesh adsorbent. The heavy metal Fe in water decreased with an effectiveness rate of 99.5% within 5 minutes of contact time. The concentration of Fe met the quality standards, both in adsorption using 60 and 100 mesh adsorbents. The concentration of Mn did not meet the quality standards. The effectiveness rate of reducing Mn was only 48.6% within 15 minutes of contact time.